Psychosocial risks in the healthcare and long-term care sectors: Evidence review and trade union views - Clara Llorens Serrano; Claudia Narocki; Clara Gual; Barbara Helfferich; Paula Franklin (European Trade Union Institute (ETUI), 2022)
Work-related psychosocial risks (PSR) are a major contributor to the burden of disease in Europe. The stress mediated health impacts of PSR are evident in the healthcare and long-term care (LTC) sectors and were brought to everyone's line of sight by the Covid-19 pandemic. While the effects of these risks manifest at the individual level as physical and mental health problems, the sources and factors are found in work organisation and employment conditions. Consequently, effective prevention of PSR operates at the collective level. This report provides an evidence overview of PSR in the healthcare and LTC sectors as well as an analysis of interview data collected from trade unions on this critical issue during the pandemic. Based on the review and the data analysis, the paper outlines the main sources of PSR and illustrates them with the voice of worker representatives. The evidence shows the deterioration of working conditions in these sectors due to the use of New Public Management methods that are an ill-fit to the reality of care work and the continuing devaluation of the work done in these feminised sectors. A discussion is provided on some PSR prevention and mitigation measures and the critical issues that must be addressed in occupational safety and health, as well as in employment policies, to ensure the right of health and care workers to safe and healthy workplaces.
Keywords: 330